TPM implementation and maintenance strategic plan: a case study - Pinto, G. (2020)
Maintenance has assumed an increasing importance in the reorganization of the industrial sector. However, there are several companies where a maintenance strategic plan needs to be implemented. This work was developed in an industrial context, in a company of Clutches and Hydraulic Controls. The focus was the implementation of a strategic plan for maintenance. The methodology chosen was Total Productive Maintenance (TPM) and the cells chosen for implementation were CNC Lathes and CNC Machining Centers. The TPM uses some maintenance activities, whose come from preventive maintenance (PM), and focuses on eliminating efficiency losses. The main problems of the cell equipment were analyzed and eliminated. Through the analysis of maintenance manuals and internal know-how, autonomous maintenance (AM) procedures and preventive maintenance plans have been created to be executed following a given timeframe. At the end of the study, the results were clearly positive due to the corrective and preventive maintenance. There was a decrease in breakdowns due to failure by 23% for CNC lathes and by 38% for CNC machining centers, which resulted in an evident increase in machine availability and OEE (Overall Equipment Effectiveness) improved by 5%.